Salvage brachytherapy for local recurrence of cancer after definitive irradiation: a GEC-ESTRO narrative review - Hannoun-Levi, J. M.; Strnad, Vratislav; Eminowicz, G.; de Iturriaga, A. Gomez; Smanykó, V.; Tagliaferri, L.; Stewart, A.; Siebert, F. A. (Radiotherapy and Oncology, 2025)
The number of irradiated cancer survivors is increasing; mainly for breast, prostate, head-and-neck, uterine and rectal cancers. Due to multiple factors including life expectancy, increasing cancer incidence and intensive cancer treatment improvements, cancer re-irradiation is an increasing phenomenon. Local recurrence of cancer after after definitive irradiation represents one of the most challenging therapeutic scenarios. The goal is to deliver to a pre-irradiated volume, a high dose (achieving secondary local control) while sparing organs at risk from deleterious over-dose (side effects). Among the different re-irradiation techniques, salvage brachytherapy (BT), due to its “Trojan horse” concept, delivers the dose directly inside the target volume with a sharp dose fall-off and low integral dose compared to external beam radiotherapy techniques. GEC-ESTRO aims to report a narrative review of the literature for salvage BT-based cancer re-irradiation for the most frequent cancers (PubMed search key words: local recurrence treatment, re-irradiation, brachytherapy, breast, prostate, head and neck, uterine and rectal cancers). GEC-ESTRO working group representatives reported for each anatomical site; recommendations for patient selection, oncological outcomes and toxicity for salvage BT. Due to its unique physical properties in terms of dose distributions, BT represents a valuable treatment option for cancer local recurrence. For all indications of salvage BT, patient selection is crucial. Shared decision making with the patient about efficacy / benefit and all potential risks represents a key point of the therapeutic decision-making process.
CRIS-Team Scopus Importer:2025-06-13
Keywords: Breast cancer; Gynaecologic cancer; Head and neck cancer; Local recurrence; Prostate cancer; Rectal cancer; Salvage brachytherapy